Epidemiological study of Mycoplasma gallisepticum and Mycoplasma synoviae: cases from laboratories in Malaysia from 2012- 2017 - Lim, P. X.; Nik Mohd Azmi, Nik Mohd Faiz (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2018)
Mycoplasma gallisepticum (MG) and Mycoplasma synoviae (MS) are ubiquitous in major poultry producing countries. Both organisms can cause wide range of complications especially respiratory and joint problems that lead to significant economic losses to the poultry industry such as production losses, mortalities, condemnations and cost of medications. In this study, the objective was to analyse the epidemiology of MG and MS cases from data of four diagnostic laboratories in Malaysia. Bacteriology, serology and molecular detection data from samples submitted to these laboratories from 2012 to 2017 were collected. Results were analysed for laboratory tests, time trends, geographical distribution, age group and purpose of flock. In total, 54863 samples were submitted to the laboratories for analysis in the study period. The percentage of Mycoplasma sp. isolated via bacterial culture isolation is 7.5% from samples collected. Meanwhile, MG and MS data shows 54% and 28% from serology detection as well as 28% and 37% based on PCR tests respectively. MG and MS are increasing throughout the 6 years duration, and more often involving older age flock. The high number of Mycoplasma infection cases in poultry flocks in Malaysia warrants improved strategies on control and prevention in the future.